Demokrasi dan Hak Asasi Manusia - Sari, Estika (Jurnal Demokrasi, 2003)
Most people in the world have felt interested in the themes of Democracy and Human Rights for a long time ago, since the Ancient Greek period until nowadays. Based on this, this article tries to elaborate some aspects connecting with the meaning of democracy, the relationship of democracy and human rights, and what the prospect of democracy and human rights in Indonesia is. Kata Kunci: Demokrasi, Hak Asasi Manusia